The application of mapinfo in managing material and waste at construction sites - Yip, Desmond Teck Wing (2006)
Many countries nowadays have serious problems concerning site layout for locating the construction materials and waste. Construction materials and waste should be managed properly especially for high rise buildings. As such, Geographic Information System (GIS) has been applied in the construction management. GIS is a software-based technology that is now thriving in Malaysia. It has been implemented in many agencies and department for various applications such as military, hydrological modeling and environmental monitoring. Managing the materials data that is needed at construction site by using conventional method is a laborious task. The implementation of GIS in construction management may improve the traditional method in the preparation of the geographic information. MapInfo was chosen as a software to develop a database system for construction materials and waste. Tools available within MapInfo were utilized to produce a system which can help the project manager to make decison to locate the materials and waste in the construction site. However, the software is limited to simple analysis but nonetheless is able to provide a data storage system that is needed in construction management. In this study, two construction sites have been choosen, which are, MPJBT and KIPark. Construction site plan were taken from the project manager and digitalize using AutoCAD. The digitized site plan were then input into MapInfo. The software is able to produce analysis according to the requirements and conditions given by the project manager. The requirements given by the project manager usually is based on their experience, safety purposes and suitability of the construction site. Project managers can use the functions within MapInfo to allocate the suitable location to place the materials and waste on their construction site. So MapInfo is a suitable tool in managing materials and waste at construction sites.